Ultrafast Charge and Triplet State Formation in Diketopyrrolopyrrole Low Band Gap Polymer/Fullerene Blends: Influence of Nanoscale Morphology of Organic Photovoltaic Materials on Charge Recombination to the Triplet State - René M. Williams; Hung-Cheng Chen; Daniele Di Nuzzo; Stephan C. J. Meskers; René A. J. Janssen (Journal of Spectroscopy)
Femtosecond transient absorption spectroscopy of thin films of two types of morphologies of diketopyrrolopyrrole low band gap polymer/fullerene-adduct blends is presented and indicates triplet state formation by charge recombination, an important loss channel in organic photovoltaic materials. At low laser fluence (approaching solar intensity) charge formation characterized by a 1350 nm band (in ~250 fs) dominates in the two PDPP-PCBM blends with different nanoscale morphologies and these charges recombine to form a local polymer-based triplet state on the sub-ns timescale (in ~300 and ~900 ps) indicated by an 1100 nm absorption band. The rate of triplet state formation is influenced by the morphology. The slower rate of charge recombination to the triplet state (in ~900 ps) belongs to a morphology that results in a higher power conversion efficiency in the corresponding device. Nanoscale morphology not only influences interfacial area and conduction of holes and electrons but also influences the mechanism of intersystem crossing (ISC). We present a model that correlates morphology to the exchange integral and fast and slow mechanisms for ISC (SOCT-ISC and H-HFI-ISC). For the pristine polymer, a flat and unstructured singlet-singlet absorption spectrum (between 900 and 1400 nm) and a very minor triplet state formation (5%) are observed at low laser fluence.